Pseudomonas exotoxin coupled to a monoclonal antibody against ovarian cancer inhibits the growth of human ovarian cancer cells in a mouse model. - Willingham, M C (1987)
In an effort to devise an alternative treatment for human ovarian cancer, we have isolated a monoclonal antibody (OVB-3) that reacts with all ovarian cancers tested (10/10) but few normal tissues. An immunotoxin produced by coupling OVB-3 to Pseudomonas exotoxin kills ovarian cancer cells in tissue culture and prolongs the life of animals bearing human ovarian cancers. These data suggest that this immunotoxin should be evaluated as a treatment for ovarian cancer in women.